Ta’liîm al-Lughah al-‘Arabiyyah bi Istikhdâm Minashah WhatsApp fî Manzhûr Ridhâ Thalabah - Nur Qomari (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
This study aims to describe the satisfaction of PKPBA students with the use of the WhatsApp platform in learning Arabic. The Learning Arabic PKPBA consist of Istima’ Learning, Kalam Learning, Qiroah Learning, Kitabah Learning Mufradat Learning and Tarakib Learning. This research uses descriptive statistical analysis method in processing the data. The population of this research is PKPBA students who are at the Faculty of Humanities UIN Maulana Malik Ibrahim Malang, amounting to 400. Researchers took 61 students as samples of this study. The results of this study indicate that the satisfaction of PKPBA students towards learning Arabic using WhatsApp is very high. Maharah Istima's learning got a satisfaction score of 52.8%', Kalam got a satisfaction score of 60.8%, Qiroah got a satisfaction score of 57.1%, Kitabah got a satisfaction score of 56.1%, Mufradat got a satisfaction score of 31.2% and Tarakib got satisfaction value 53.3%.